PENERAPAN PEMBELAJARAN KONTEKSTUAL SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA KONSEP PEMBAGIAN PADA PESERTA DIDIK KELAS 3A SD VITA SURABAYA - Silvano Yugi Ananta; Lina Listiana; Diah Eka Sulistyorini (PROCEEDING UMSURABAYA, 2024)
This Classroom Action Research aims to improve the ability to understand the concept of division arithmetic operations of students in class III A SD VITA Surabaya using a contextual learning approach. This research was conducted in two cycles, namely Cycle I and Cycle II, each cycle consisting of the stages of planning, implementation, observation and reflection. The assessment instruments used in this study were formative tests and observation sheets related to learning motivation. The increase occurred from Cycle I to Cycle II, which was 16%. So it can be concluded that contextual learning is effective to improve the ability to understand the concept of division arithmetic operations in students of class III A SD VITA Surabaya.